2016
DOI: 10.3390/molecules21030360
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids, Antioxidant Potential, and Acetylcholinesterase Inhibition Activity of the Extracts from the Gametophyte and Archegoniophore of Marchantia polymorpha L.

Abstract: Marchantia polymorpha L. is a representative bryophyte used as a traditional Chinese medicinal herb for scald and pneumonia. The phytochemicals in M. polymorpha L. are terpenoids and flavonoids, among which especially the flavonoids show significant human health benefits. Many researches on the gametophyte of M. polymorpha L. have been reported. However, as the reproductive organ of M. polymorpha L., the bioactivity and flavonoids profile of the archegoniophore have not been reported, so in this work the flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…The chemicals were the same with previous report [14]. Rutin (purity > 99.0%), 2,2-Diphenyl-1-picrylhydrazyl (DPPH), 2,2’-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), Nitrotetrazolium blue chloride (NBT), phenazine methosulfate (PMS), nicotinamide adenine dinucleotide (NADH), 5, 5’-dithiobis-(2-nitrobenzoic acid) (DTNB) and 2,4,6-tri-2-pyridyl-s-triazine (TPTZ) were purchased from Sigma Co. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The chemicals were the same with previous report [14]. Rutin (purity > 99.0%), 2,2-Diphenyl-1-picrylhydrazyl (DPPH), 2,2’-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), Nitrotetrazolium blue chloride (NBT), phenazine methosulfate (PMS), nicotinamide adenine dinucleotide (NADH), 5, 5’-dithiobis-(2-nitrobenzoic acid) (DTNB) and 2,4,6-tri-2-pyridyl-s-triazine (TPTZ) were purchased from Sigma Co. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16] These findings suggest that natural products, including herbal medicines, may be complementary and alternative approaches to Western medicine for the treatment of Alzheimer's disease. Although recent studies of Alzheimer's disease therapy have been shifting to other targets, such as amyloid-β, 17) Tau, 18) reactive oxygen species, 19) and the blood-brain barrier, 20) AChE inhibitors are still the first choice for treating patients with AD.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we further analyzed the chemical composition of SC 1,3‐butanediol extract by UHPLC‐QTOF; finally, 12 kaempferol compounds were found in SC 1,3‐butanediol extract and kaempferol 3‐O‐[α‐rhamnopyranosyl‐(1→6)‐β‐glucopyranoside] and kaempferol‐3,7‐O‐α‐L‐dirhamnoside were two major compounds. In fact, kaempferol belongs to the flavonoids, previous a large number of works indicated that flavonoids have anti‐tyrosinase, anti‐melanogenic, antioxidant, and anti‐inflammatory activity . It is well known that tyrosinase catalyzes tyrosine and eventually leads to the production of melanin, so compounds with similar structures to tyrosinase compete to inhibit the activity of tyrosinase.…”
Section: Discussionmentioning
confidence: 99%
“…3 In order to further develop the value of shell of Camellia oleifera Abel, in this study, we aim to examine the ability of SC extracts to inhibit in vitro tyrosinase activity and and anti-inflammatory activity. [16][17][18][19] It is well known that tyrosinase catalyzes tyrosine and eventually leads to the production of melanin, so compounds with similar structures to tyrosinase compete to inhibit the activity of tyrosinase. Both kaempferol and tyrosine have similar phenolic hydroxyl structure, which will directly affect the first step of tyrosinase-catalyzed reaction.…”
Section: Discussionmentioning
confidence: 99%